Measurement of Shared Social Identity in Singing Groups for People With Aphasia - Tarrant, Mark; Lamont, Ruth A.; Carter, Mary; Dean, Sarah G.; Spicer, Sophie; Sanders, Amy; Calitri, Raff (Frontiers in Psychology, 2021)
Community groups are commonly used as a mode of delivery of interventions for promoting health and well-being. Research has demonstrated that developing a sense of shared social identity with other group members is a key mechanism through which the health benefits of group membership are realised. However, there is little understanding of how shared social identity emerges within these therapeutic settings. Understanding the emergence of shared social identity may help researchers optimise interventions and improve health outcomes. Group-based singing activities encourage coordination and a shared experience, and are a potential platform for the development of shared social identity. We use the ‘Singing for People with Aphasia’ (SPA) group intervention to explore whether group cohesiveness, as a behavioural proxy for shared social identity, can be observed and tracked across the intervention. Video recordings of group sessions from three separate programmes were rated according to the degree of cohesiveness exhibited by the group. For all treatment groups, the final group session evidenced reliably higher levels of cohesiveness than the first session (t values ranged from 4.27 to 7.07; all p values < 0.003). As well as providing confidence in the design and fidelity of this group-based singing intervention in terms of its capacity to build shared social identity, this evaluation highlighted the value of observational methods for the analysis of shared social identity in the context of group-based singing interventions.